AWS in motion (Manning Publications, 2017)
"WS in Motion guides you through your first steps of deploying a web application on AWS, teaching you the basics of the AWS ecosystem. You'll start by setting up a free AWS account, and then you'll learn how a typical web stack runs and scales in the cloud in a manner that can beat any physical data center! In nearly 3 hours of easy-to-follow video lessons, you'll explore the many services available in the AWS ecosystem. Designed for system administrators and DevOps engineers looking to start developing and deploying applications on the AWS platform. You need to be familiar with the basic components of a web application and the general terminology of a network."--Resource description page